Behandling av fraseologi i Norsk Ordbok - Vikør, Lars S. (Nordiske Studier i Leksikografi, 2007)
Treatment of phraseology is an important part of lexicography, which has been given extensive attention during the most recent decades. In Norsk Ordbok (‘Norwegian Dictionary’), as in many sister projects, this has been done less systematically than desirable in the past. At present, when the project is being thoroughly revised, a systematization has been undertaken. This is not yet finished, but here I introduce a typology of Norwegian phrases related to three possible ways of presenting them in the dictionary: as separate lemmas (only recommended for foreign phrases imported integrally into Norwegian), as sublemmas (roughly for the most idiomatic phrases) and as editorial examples (mostly collocations or looser word combinations, and expressions with a normal sentence structure). The typology is based on grammatical criteria, and for each category examples are given, followed by an indication of the most suitable lexicographic treatment according to the view of the author.